2018
DOI: 10.1177/1049909118797283
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Adverse Effect Profiles of Corticosteroids in Palliative Care Patients

Abstract: Recognition of corticosteroid induced adverse effect profiles and possible management strategies is crucial to optimal symptom management in palliative care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Evidence for their efficacy is weak, although a Cochrane systematic review found that some studies showed a beneficial effect on cancerrelated pain after 1 week of treatment. 83 In light of the many well-documented adverse effects, 84 the likely benefit to risk ratio for the individual needs careful consideration.…”
Section: 'Don't Know'mentioning
confidence: 99%
“…Evidence for their efficacy is weak, although a Cochrane systematic review found that some studies showed a beneficial effect on cancerrelated pain after 1 week of treatment. 83 In light of the many well-documented adverse effects, 84 the likely benefit to risk ratio for the individual needs careful consideration.…”
Section: 'Don't Know'mentioning
confidence: 99%
“…In clinical practice, corticosteroids are widely used in cancer patients in the palliative phase to alleviate inflammatory pain, relieve nausea, reduce peritumoral oedema, increase appetite, reduce itching and to reduce fatigue [72,73]. As shown above, clinical trials investigating the effect of corticosteroids on fatigue in patients with advanced or metastatic cancer are scarce and partly based on observational studies [74,75].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Prices from goodrx.com . Information from Allen et al, 2016 ; Collis & Mather, 2015 ; Digges et al, 2018 ; Harder et al, 2019b ; Hendren et al, 2015 ; Hernandez et al, 2015 ; Jaward et al, 2019 ; Kaneishi et al, 2016 ; Khanna et al, 2019 ; Khoo & Quinlan, 2016 ; Langley-DeGroot et al, 2015 ; Lovell et al, 2018 ; MacKintosh, 2016 ; Prohotsky et al, 2014 ; Prommer, 2012 ; Riordan et al, 2019 ; van der Meer et al, 2014 ; Wiebe, 2012 . …”
Section: Select Antiemetics and Adjuvant Agents Based On Probable Benunclassified
“…Corticosteroids are inexpensive and useful for N/V related to primary or metastatic brain tumors, MBO, or with unexplained N/V ( Collis & Mather, 2015 ; Glare et al, 2011 ; Hendren et al, 2015 ). The duration of action of dexamethasone is 36 to 72 hours; prednisone and methylprednisolone act for 12 to 36 hours ( Jaward, O’Neil, Marks, & Smith, 2019 ). Dexamethasone is the most potent anti-inflammatory: dexamethasone at 0.75 mg ≈ prednisone at 5 mg ≈ methylprednisolone at 4 mg.…”
Section: Select Antiemetics and Adjuvant Agents Based On Probable Benmentioning
confidence: 99%
See 1 more Smart Citation